(untitled) (Research, Society and Development, 2021)
Introduction: Functional dyspepsia is a challenging gastrointestinal syndrome due to the various factors that may generate it and the criteria required to diagnose it. However, it is possible to understand the epidemiological and clinical profile of these patients, as well as to identify the influence of some conditions on their manifestations. Objective: to assess the prevalence of functional dyspepsia and its characterize the epidemiological and clinical aspects. Methodology: prospective, cross-sectional, survey-type study, with dyspeptic patients referred to the upper digestive endoscopy service. The sample consisted of 859, with a clinical diagnosis of dyspepsia, and self-explanatory questionnaires were reported: sociodemographic, Beck Anxiety Inventory, Beck Depression Survey and the ROMA III questionnaire. Results: 36 (4.19%) of the total respondents met ROMA IV criteria for functional dyspepsia, which encompasses two different clinical syndromes: postprandial discomfort syndrome and epigastric pain syndrome. The average age group was 31.5 years old (19.2-39.7), 23 (63.9%) were from Aracaju, 32 (88.8%) were female, 21 (60%) were single and 19 (54.3%) considered themselves brown. We identified 19 (52.8%) patients with anxiety and 9 (25%) with depression. According to the criteria, 10 (27.8%) postprandial discomfort syndrome, 07 (19.4%) epigastric pain syndrome and 19 (52.8%) both simultaneous clinical subtypes. Conclusion: a functional dyspepsia was more prevalent among women, single dependents, brown skin color and people with anxiety. There was no statistical significance regarding the type of clinical presentation, although the simultaneous manifestation of the two subtypes was more prevalent.